Reframing the Nineteenth Century - Pinto, Rochelle (2018)
No longer determined exclusively by the economic fortunes of the empire, the history of the nineteenth‑century Portuguese colonies in India and the Indian Ocean region has been sufficiently elaborated for some heuristic frameworks to emerge. Histories of medicine, anthropology, politics, print, migration and slavery underscore the importance of non-statist narratives as they trace the movement of people, goods and ideas along formal and informal networks, often under the ascendant British colonial power. Along with studies on visual and spatial culture and agrarian policy, these narratives have helped delineate distinctive and contesting attributes that characterise the nineteenth century. The century continues to pose a historiographic challenge as it both draws from and contests the dominant theoretical accounts of colonialism.